Communication strategies of male and female students - Mariana Ulfa (Jurnal Linguistik Terapan, 2016)
This paper is aimed at investigating the types of communication strategies employed by male and female students of Electronic engineering study program. Communication strategies are strategies applied by learners to assist them to overcome problems during communication. The subjects of this research are 20 students of second grade Diploma III Electronic engineering study program. The students were given task to do presentation about electronic home appliances. The presentations were recorded and later the communication strategies will be analyzed. This research uses Faerch and Kasper (1983) typology of communication strategies which divide communication strategies into two kinds, namely achievement and reduction strategies. Achievement strategies are employed when learners decide to keep the original communicative goal but compensate for insufficient means or make the effort to retrieve the required item. The sign of reduction strategies is when learners to do away with a problem. The strategies can be seen through the learners giving up part of his/her communicative goal.